Analysing the impact of personal traits of credit assessors on credit risk assessment. (13th January 2022) - Kaur, Sandeepa
This paper examines enviable personal attributes of expert credit assessors. The empirical information comprised of 26 experienced credit assessors' interview responses on a personal attribute survey obtained from various Indian banks conducted in November 2020. After examining the personal interviews and based on the outcomes on these meetings, a measurement was built. Based on unstructured interviews a survey questionnaire was developed for enquiring 27 attributes of inquisitors that may affect the credit granting process. Kruskal Wallis and factor analysis has been applied to examine the existence of patterns in the responses provided by specialists and to calculate the relative weights of various indicators. The outcomes demonstrate that the specialist inquisitors are inclined to give higher however less scattered evaluations of the attributes. By exploratory factor analysis credit assessors' responses were consolidated into: competence, core skills and interpersonal skills. The empirical discoveries ought to enhance our comprehension of specialists performing credit evaluations.